In situ analysis of residues resulting from laboratory impacts into aluminum 1100 foil: Implications for Stardust crater analyses - Wozniakiewicz, P.; Kearsley, A.; Burchell, M.; Foster, N.; Cole, M.; Bland, Phil; Russell, S. (John Wiley & Sons, Inc., 2009)
The encounter between the Stardust spacecraft and particles from comet 81P/Wild 2 gave impacts at a relative velocity of 6.1 km s−1 and near perpendicular incidence to the collector surface. Such conditions are well within the performance limits of light gas gun laboratory simulations. For this study, two series of shots were conducted at the University of Kent, firing magnesium silicates (Mg end-member forsterite, enstatite, diopside and lizardite), followed by a suite of increasingly Ferich olivines (through to Fe end-member fayalite) into Stardust flight-spare foils. Preserved residues were analysed using scanning electron microscopy combined with energy dispersive X-ray analyses (SEM/EDX). X-ray count integrals show that mineral compositions remain distinct from one another after impact, although they do show increased scatter. However, there is a small but systematic increase in Mg relative to Si for all residues when compared to projectile compositions. While some changes in Mg: Si may be due to complex analytical geometries in craters, there appears to be some preferential loss of Si. In practice, EDX analyses in craters on Stardust Al 1100 foil inevitably include contributions from Fe- and Si-rich alloy inclusions, leading to further scattering of element ratios. Such inclusions have complicated Mg: Fe data interpretation. Compositional heterogeneity in the synthetic olivine projectiles also introduces data spread. Nevertheless, even with the preceding caveats, we find that the main groups of mafic silicates can be easily and reliably distinguished in EDX analyses performed in rapid surveys of foil craters, enabling access to a valuable additional collection of cometary materials.